PTH-217 Spinal infections among patients with long term central venous catheters for home parenteral nutrition: a descriptive case series. (22nd June 2015) - Topan, R; Lightman, E; Small, M; Ambrose, T; Nightingale, JM; Gabe, SM
Abstract : Introduction: Long-term central venous catheters for home parenteral nutrition (HPN) carry a risk of recurrent bacterial colonisation and catheter related sepsis (CRS). 1 Spinal infections following an episode of CRS are uncommon but may be underreported or overlooked due to the high incidence of osteoporotic fractures in this cohort. 2 We aimed to determine the frequency and describe cases of spinal infections in HPN patients at our institution. Method: We performed a retrospective review of all spinal infections presenting in our HPN patients between January 2010 and October 2013, a cohort of approximately 270 patients. Data were extracted on basic demographics, indication for and duration of HPN, means of venous access, history of presentation and management. Results: The CRS rate was 0.9 per 1000 catheter days. Six patients were identified (mean age 65 years, 5 male) with spinal infection, a rate of 0.02 per 1000 catheter days. Duration with current CVC ranged from 5 months to 2 years. All patients presented with spinal pain; 5/6 cervical, 1/6 thoracic. All patients had a normal white cell count and differential, and in only 1 case was the CRP elevated. In 4 cases an organism was isolated at the time of presentation from blood cultures taken centrally and/or peripherally – commonly staphylococcal species. All patients had contrast-enhanced magnetic resonance imaging (MRI) with features compatible with spinal infection and in two patients a repeat MRI demonstrated resolution of changes. In three patients a disc biopsy was performed yielding one negative culture, one microbiological correlation with blood cultures and a single positive culture (unknown isolate). All patients received three months of intravenous antibiotic therapy augmented with surgery or conservative management on a case-by-case basis. The CVC was removed in 4/6 patients at presentation, with salvage in the remaining two. Conclusion: Spinal infections associated with long-term CVC for HPN should be considered in patients presenting with spinal pain. They are often of insidious onset and may present with normal inflammatory markers which may contribute to delayed or missed diagnoses that together with differences in the definition of CRS 1 may partially explain the poor representation in the current HPN-related literature. 3 Gold-standard imaging is with contrast-enhanced MRI with formal biopsy decided on an individual basis. Management should involve prolonged antibiotics and liaison with microbiology and neurosurgery. Multidisciplinary discussion on CVC salvage is important especially in cases of difficult vascular access. Disclosure of interest: None Declared. References: Reimund JM, et al. Clin Nutr. 2002;21(2):33–38 Haderslev KV, et al. JPEN 2004;28(5):289–294 Huard G, et al. J Clin Med Res. 2014;6(4):272–277